2007
DOI: 10.1063/1.2771058
|View full text |Cite
|
Sign up to set email alerts
|

Broadband all-optical ultrasound transducers

Abstract: A broadband all-optical ultrasound transducer has been designed, fabricated, and tested for high-resolution ultrasound imaging. It consists of a two-dimensional gold nanostructure on a glass substrate, followed by a 3μm polydimethylsiloxane layer and a 30nm gold layer. The signal to noise ratio of a pulse-echo signal is over 10dB in the far field of the transducer, where the center frequency is 40MHz with −6dB bandwidth of 57MHz. The potential for high-frequency ultrasound arrays using this technology is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 20 publications
0
71
0
Order By: Relevance
“…Whilst all-optical ultrasound images have previously been obtained [5][6][7][8], those in this study were significant in terms of the detail with which tissue microstructure was visualised, and the compactness of the probe with which they were acquired. The high performance of the probe in this study stemmed from a combination of the high ultrasound pressures transmitted by the optically absorbing film and the high sensitivity of the concave FP ultrasound sensor.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Whilst all-optical ultrasound images have previously been obtained [5][6][7][8], those in this study were significant in terms of the detail with which tissue microstructure was visualised, and the compactness of the probe with which they were acquired. The high performance of the probe in this study stemmed from a combination of the high ultrasound pressures transmitted by the optically absorbing film and the high sensitivity of the concave FP ultrasound sensor.…”
Section: Discussionmentioning
confidence: 96%
“…To achieve high optical-ultrasound transduction efficiency, a material with a high optical absorption coefficient and a high thermal expansion coefficient is desirable [9]. Recent studies have highlighted the efficacy of composite materials that comprise optical absorbers integrated within elastomers [5,10,11]. The authors recently demonstrated a method for creating ultrasound transmitters at the tip of an optical fiber using a composite material comprised of functionalised multi-walled carbon nanotubes (CNTs) and polydimethylsiloxane (PDMS) [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34][35] Next, we present the current development of multimodality imaging combined with all-optical PAI. At the end, an outlook about all-optical dual-mode imaging system is present.…”
Section: Introductionmentioning
confidence: 99%